An Analysis of Students’ Difficulties in Comprehending Hortatory Exposition Text at SMA Adabiah 2 - Asrul Mulyadin (Jurnal Ilmiah Pendidikan Scholastic, 2023)
The aims of this research are to describe students’ difficulties in comprehending hortatory exposition text at SMA Adabiah 2 Padang. The subject of this research was the second year students of SMA Adabiah 2 Padang at 2022/2023 academic year. Out of 267 students, 20% of them were chosen to be the sample by using the cluster random sampling technique. The data were collected by using a reading test and interview guideline. The results of this research show that from 232 total frequent for each indicator, the highest percentage made by the students was in identifying language feature question. There were 130 total difficulties with the percentage 56, 03%. While the lowest percentage made by the students was in identifying thesis statement questions. There are 99 total difficulties with the percentage 42, 67%. Related to the cause of difficulties, it was the language factors that students difficult to understand the long sentence and vocabulary in the text, and the last factor was the lack of reading strategies. It can be concluded that the students of SMA Adabiah 2 find it difficult in comprehending hortatory exposition text. It proves that more than 50% of students cannot answer the question of hortatory exposition text correctly. It caused the student difficult to understand the long sentence and the vocabulary in the text and also the lack of reading strategies itself.